Muddy sensemaking: Making sense of socio-emotional skills amidst a vague policy context - Raquel Muñiz (Arizona State University, 2020)
Education laws and policies have moved toward promoting socio-emotional (SEL) skills, adopting numerous terminologies in their standards. However, the incremental change has left compensatory education practitioners who are committed to promoting SEL opportunities with little guidance when the programs' governing policies do not include language acknowledging the importance of SEL to student success. Additionally, the ongoing debate in the SEL field about which taxonomies might best capture the skills and the lack of conceptual clarity offers these practitioners little additional guidance. Drawing on sensemaking theory, this case study examined how practitioners in a compensatory education program made sense of SEL skills through their practice. The study used a case-based design with multiple methods, namely, document review, observations, and pre- and post-program semi-structured interviews. The study employed sensemaking theory and CASEL's SEL framework in the thematic analysis of the documents, observations, and interviews to understand how practitioners made sense of the concept of SEL. The findings indicate three key aspects important in the practitioners' sensemaking process: the local environment established by the federal policy and the leaders' policy interpretation, which emphasized the importance of SEL skills; their articulation of their conceptualization of SEL skills at the beginning of the program; and the usefulness of an SEL skills conceptual framework. I discuss the policy and equity implications at the federal and local level.